High school EFL Khmer students’ challenges and solutions in learning English letter writing : - Phù, Thị Hồng Châu (Trường Đại học Cần Thơ, 2020)
This study was conducted at a high school in Kien Giang Province in the school year 2019-2020 to investigate the challenges and solutions of Khmer students while learning to write English letters. This research used an integrated research method including qualitative and quantitative methods. The quantitative research method was used to identify Khmer students' challenges or hereby called difficulties in English writing skills. The qualitative research method was used to investigate Khmer students' solutions to their problems. The process of analyzing the results in turn was to analyze the results of the two letter writings, then the questionnaire analysis and finally the interview result analysis. The results showed that Khmer students had difficulty writing skills. These difficulties related to the Khmer students’ ways of learning and teachers' teaching methods. Among these difficulties, the results indicated that most of the students participating in the study found it beneficial to understand and use English language skills and considered this to be the most important difficulty. The results also showed that Khmer students were interested and aware of the different solutions, in which they paid special attention to the teaching method of the teachers and regarded this as an effective solution. In addition, Khmer students also proposed other solutions related to the curriculum, textbooks, etc.